The flower market with no florists - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The residential neighbourhood of Bonapriso, in Douala, Cameroon, once had a thriving flower market with about 50 stands. With a monthly rental of h 45, they were filled with lilies-of-the-valley, lilies, roses and daisies. Several kilometres away, a...